(untitled) (International Journal of Nursing Education, 2020)
Stroke is a medical emergency that the patients of it ideally should have received stroke management ?3hours since the attack. Emergency situations can occur at anytime, thus the health cadres participation inminimizing pre-hospital delay through FAST method is needed. In order to make the cadres have knowledge,positive attitudes, and good practices about FAST, the rational model-based training was conducted. The aimof this study was to analyze the effectiveness of rational model-based training on the health cadres’ changeson knowledge, attitudes, and practices in the stroke symptoms detection using FAST. This study used quasiexperimentalresearch design through pretest-posttest control group design. 50 respondents were dividedinto intervention and control groups. Data analysis used independent sample t-test and mann whitney test.The results show that there were differences in attitude and practices changes between the intervention andthe control groups after training, with p values 0.009 and 0.000. There was no any difference in the retentionof knowledge, attitudes, and practices in both groups, the p value was 0.849; 0.626;0.456.